2012
DOI: 10.4269/ajtmh.2012.11-0485
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Oropouche Orthobunyavirus in the Cerebrospinal Fluid of Three Patients in the Amazonas, Brazil

Abstract: Abstract. Oropouche fever is the second most frequent arboviral infection in Brazil, surpassed only by dengue. Oropouche virus (OROV) causes large and explosive outbreaks of acute febrile illness in cities and villages in the Amazon and Central-Plateau regions. Cerebrospinal fluid (CSF) samples from 110 meningoencephalitis patients were analyzed. The RNA extracted from fluid was submitted to reverse transcription-polymerase chain reaction and sequencing to identify OROV. Three CSF samples showed the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
0
12

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 13 publications
3
58
0
12
Order By: Relevance
“…Nucleotide sequence analysis shown that the OROV from the CSF of these 3 patients belonged to genotype 1, the same as those previously reported for the virus in the Amazonas (18) .…”
Section: Oropouche Feversupporting
confidence: 64%
See 1 more Smart Citation
“…Nucleotide sequence analysis shown that the OROV from the CSF of these 3 patients belonged to genotype 1, the same as those previously reported for the virus in the Amazonas (18) .…”
Section: Oropouche Feversupporting
confidence: 64%
“…The RNA extracted from CSF was submitted to a reverse transcription-polymerase chain reaction, which revealed the OROV genome in 3 samples, thus confi rming that this virus is also a causative of central nervous system (CNS) infection in the State of Amazonas. All 3 patients were adults, and 2 of them had other diseases affecting CNS and immune systems, neurocysticercosis and acquired immunodefi ciency syndrome, respectively (18) .…”
Section: Oropouche Fevermentioning
confidence: 99%
“…Já foi relatada a transmissão do EEEV na forma de aerossol, sendo considerado como um dos seis agentes infecciosos que constituem a lista de mais alto nível de ameaça para utilização como agente de bioterrorismo 43 . Em outro estudo realizado em Manaus, foram identificadas três amostras positivas em 110 amostras de líquido cefalorraquidiano analisadas, sendo imputado ao vírus a causa da doença do sistema nervoso central 46 .…”
Section: Vírus Encefalite Equina Do Leste (Eeev)unclassified
“…Culicoides (Haematomyidium) paraensis (Goeldi) is incriminated as a vector of oropouche (ORO) virus (Bastos et al 2012). In Brazil, ORO is the etiological agent of the second most frequent cause of febrile arboviroses (Bastos et al 2012). Moreover, species in the genera Atrichopogon Kieffer and Forcipomyia Meigen are ectoparasites of adult and immature insects, for example Lepidoptera and Odonata (Kawahara et al 2006, Koptur et al 2013, Nielsen et al 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Culicoides (Hoffmania) insignis Lutz is a vector of Bluetongue virus (BTV) of domestic and wild ruminants in the Neotropics (Tanya et al 1992). Culicoides (Haematomyidium) paraensis (Goeldi) is incriminated as a vector of oropouche (ORO) virus (Bastos et al 2012). In Brazil, ORO is the etiological agent of the second most frequent cause of febrile arboviroses (Bastos et al 2012).…”
Section: Introductionmentioning
confidence: 99%